Open Access Repositories in Serbia - Djokovic, Gordana Jovan (Qualitative and Quantitative Methods in Libraries; Vol 10 No 4 (2021): December issue 2021, 2022)
Created from the need to store and use deposited digital information, Open Access repositories provide access to digital content from anywhere at any time. They also provide full open access to all deposited content. Open Access repositories in Serbia have been present since 2005. when the doiSerbia system was established. It was developed through the Repository of the University of Belgrade established in 2012, until today when institutional digital repositories are rapidly developing. This paper will present the growth and development of Open Access repositories in Serbia, presenting all Open Access repositories in Serbia registered on the Registry of Open Access Repositories (ROAR) portal and Directory of Open Access Repositories (OpenDOAR), as well as the most famous software used for their maintenance (DSpace, EPrints, Fedora). The indicators will be shown statistically by the number and type of documents deposited in the displayed repositories as well as the representation of scientific fields covered by existing repositories. The paper aims to show the importance of Open Access repositories in terms of increasing visibility and citation of scientific results deposited.